2020
DOI: 10.12659/msm.923251
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine Reduces Myocardial Oxidative Stress and Alleviates Myocardial Ischemia-Reperfusion Injury by Activating Nuclear Transcription-Related Factor 2 (Nrf2)/Heme Oxygenase-1 (HO-1) Signaling Pathway

Abstract: Background:Myocardial ischemia-reperfusion injury (IRI) is an important injury mechanism of myocardial infarction. The purpose of this study was to explore the effects of L-carnitine (LC) on myocardial IRI and its mechanism. Material/Methods:The IRI model was made by ligating the left anterior descending coronary artery. Then, we injected LC intraperitoneally into the rats of the experimental group to assess the effect of LC on IRI rats by use of serum markers, Western blot, and qRT-PCR. H9c2 cells were cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Moreover, in acute conditions, such as in myocardial infarction, LC could mitigate abnormal oxidative stress condition and enhance cardiomyocytes survival. Animal studies and preliminary clinical studies seem to confirm this hypothesis [195][196][197][198]. It is important to note that these first trials suggest that LC improves antioxidative cellular defense, in particular the NRF2 pathway [198].…”
Section: From Caloric Restriction To Cr-related Nutrients: L-carnitinementioning
confidence: 78%
“…Moreover, in acute conditions, such as in myocardial infarction, LC could mitigate abnormal oxidative stress condition and enhance cardiomyocytes survival. Animal studies and preliminary clinical studies seem to confirm this hypothesis [195][196][197][198]. It is important to note that these first trials suggest that LC improves antioxidative cellular defense, in particular the NRF2 pathway [198].…”
Section: From Caloric Restriction To Cr-related Nutrients: L-carnitinementioning
confidence: 78%
“…Research has confirmed that Nrf2 protect cardiomyocytes from oxidative stress by increasing detoxification pathways, enhancing antioxidant potential and alleviating oxidative damage in various disease states (20).…”
Section: Ros-associated Mechanism Of Different Concentrations Of Pinacidil Postconditioning In the Rat Cardiac Nrf2-are Signaling Pathwaymentioning
confidence: 99%
“…A variety of other substances have been shown to exert their cardioprotective effects against myocardial I/R injury via HO-1 activation. L-carnitine, either injected intraperitoneally to rats undergoing left anterior descending (LAD) coronary artery occlusion or administered to H9c2 cardiomyoblasts exposed to hypoxia/reoxygenation, reduced oxidative stress and apoptosis likely via activation of Nrf2/HO-1 pathway [ 99 ]. Galanthamine, an alkaloid with anti-inflammatory properties, has been shown to reduce myocardial I/R injury, endoplasmic reticulum stress-related apoptosis, and myocardial fibrosis in rats via activating 5â€Č adenosine monophosphate-activated protein kinase (AMPK)/Nrf2/HO-1 pathway [ 100 ].…”
Section: Heme Oxygenase System In I/r Injury and Cytoprotectionmentioning
confidence: 99%